Oral Corticosteroids in Asthma: A Review of Benefits and Risks - Robert Schellenberg; Jonathan D R Adachi; Dennis Bowie; Jacques Brown; Lyn Guenther; Tina Kader; Graham E Trope (Canadian Respiratory Journal)
Oral corticosteroids (OCS) play an integral role in the pharmacological management of asthma, as well as a number of other inflammatory and autoimmune disorders. However, although their broad spectrum of effect is beneficial in controlling inflammation, it can also lead to undesirable effects on other cells, resulting in adverse effects. The purpose of the present review is to discuss the particular benefits of OCS and to outline the optimal role of these agents in the management of asthma, drawing on evidence-based medicine and current clinical practice guidelines. The mandate for the present review also covers an analysis of the risk:benefit ratio as it pertains to OCS use in asthma. The more common adverse effects will be discussed and weighed against the possible benefits.